Hubungan Pembelajaran Online Terhadap Tingkat Kecemasan Dan Tingkat Stress Pada Mahasiswa Keperawatan Universitas Jambi Selama Pandemi COVID-19 - Azizah, Tania Febria; Nurlinawati, Nurlinawati; Meinarisa, Meinarisa; Fitriwati, Citra Indah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: Covid-19 increase reaches 204 countries, caused learning to be carried out online so that students' anxiety and stress increased.To find out the relationship between online learning and anxiety and stress for nursing students at Jambi University during the Covid-19 pandemicMethods: This research used in this research is quantitative research with correlational research type, google form research instrument and data analysis using spearman rank test.Results: The majority of online learning is in the fairly good category (53.4%), the majority of anxiety is in the mild anxiety category (60.3%), and the majority of stress is in the mild stress category (74.0%). The relationship between online learning and student anxiety is p-value 0.008 > less than 0.05, meaning that there is a relationship between online learning and anxiety. Online learning on stress in nursing students is 0.015 < less than 0.05, meaning that there is a relationship between online learning and stress.Conclusion: Based on the results of the study, there is a relationship between online learning and the anxiety and stress of nursing students at Jambi University during the Covid-19 pandemic.